The management of personal protective equipment during the COVID-19 pandemic: The case of the province of Quebec. Issue 2 (March 2022) - Beaulieu, Martin; Roy, Jacques; Rebolledo, Claudia; Landry, Sylvain
Like other Canadian provinces, Quebec managed shortages of Personal Protective Equipment (PPE) in the early weeks of the COVID-19 pandemic. Two years later, with hindsight, what lessons can we learn from this logistics crisis? It is precisely to better understand the decisions made by the supply chain players in the province of Quebec that this paper was written. To fully understand the events, this paper first describes the Quebec healthcare system. Then it retraces the series of events and actions during the first wave, at a time when it was most challenging to procure PPE. It also specifies the main characteristics of the supply chain in the Quebec healthcare sector. Finally, it analyzed these data to come up with recommendations to help public decision makers adopt better supply chain management practices.